Resolved images of a protostellar outflow driven by an extended disk wind - Bjerkeli, Per; Wiel, Matthijs H. D. van der; Harsono, Daniel; Ramsey, Jon P.; Jorgensen, Jes K. (Nature, 2016)
Observations of the outflow associated with the TMC1A protostellar system reveal that the ‘disk wind’ model correctly explains how material is ejected from protostars.
Gesehen am 13.05.2020